ASSESSING THE SYNERGETIC EFFECT OF SELECTING THE OPTIMAL STRUCTURE OF A LOGISTICS CHAIN - Vitalii NAUMOV; Ihor TARAN; Zhumazhan ZHANBIROV; Batyrbek MUSSABAYEV; Zarina KONAKBAI (Scientific Journal of Silesian University of Technology. Series Transport)
This study tackles a critical challenge in logistics optimization: assessing the economic efficiency not only of individual entities within a logistics chain, but also the synergistic benefits that arise from their collaboration. We achieve this by proposing a methodology that evaluates the economic efficiency of interactions between participants in a logistics chain. This methodology goes beyond individual efficiency and delves into how the overall economic benefit is distributed among key stakeholders. These stakeholders include freight owners, who initiate the delivery process, forwarders who manage and optimize deliveries, carriers who physically transport goods, and freight terminals that facilitate cargo handling and storage. To ensure the methodology’s relevance to contemporary practices, we begin with a comprehensive review of recent advancements in delivery chain optimization research. We propose to measure the synergetic effect by considering delivery demand parameters, such as the weight of the consignment and the distance it needs to travel. To validate our methodology and gain practical insights, we conducted a series of experimental studies specifically tailored to the Kazakhstani transportation market. By analysing the share of the synergistic effect under varying delivery demand parameters, we were able to identify trends and patterns.